Screening of rice cultivars against Scirpophaga incertulas Walker : utilising cluster analysis as a tool to identify resistant cultivars - KEERTHIKA N; Dr.Palash Mondal (ORYZA-An International Journal of Rice, 2024)
The field experiment was conducted in the Boro season from December 2022 to April 2023 at the Institutional research farm, Institute of Agriculture, Palli Siksha Bhavana, Visva-Bharati, Sriniketan, Birbhum, West Bengal, for the screening of thirty-three rice cultivars for their resistance to yellow stem borer, Scirpophaga incertulas Walker. The experiment utilized modified percent damage values to grade these cultivars during both vegetative and reproductive stages. Early-duration cultivars displayed varied reactions, with Jaldi 13 (2) exhibiting consistent resistance (2.53% DH, 12.65% D), while others showed moderate resistance or susceptibility with deadheart percentages ranging from 4.73% to 8.51% and corresponding damage percentages between 23.65% and 42.55%. This trend extended to reproductive stages, where all early-duration cultivars demonstrated moderate to high susceptibility, with damage percentages between 30.8% and 54.5%. The mid-early duration cultivars displayed mixed responses, with Sahabhagi (4) demonstrating moderate resistance (4.92% DH) and Sukumar (3) exhibiting moderate susceptibility (8.21% DH) during the vegetative stage. These diverse reactions continued into the reproductive stage, providing a comprehensive understanding of their responses to the pest. Additionally, in medium and late-duration cultivars, a range of reactions persisted, with cultivars like Pratiksha (20) showing moderate resistance (6.63% DH) in the mid-duration category and Ajith (25) displaying moderate resistance (6.33% DH) in the late-duration category. Cluster analysis categorized the cultivars into distinct groups, showcasing a mix of resistant, moderately resistant, and susceptible types across all growth durations. Notably, cultivars like Gotra 1 (10), Parijat (14), Pushpa (17), PNR 546 (19), Pravat (23) and Gotra 2 (31) consistently demonstrated resistance or moderate resistance across different growth stages, suggesting their potential suitability in tailoring resistant breeding programs and pest management strategies against the stem borer in rice cultivation.